Registration on Line - Mhesn, Ali; Hamaidan, Mahmad; Thwib, Rafat (My University)
The aim of our project is to make the process of registration in the PPU done on line. To grant the student the flexibility that needed in the process of registration. The result of this project is a web-based software system solution that provides certain requirements according to predetermined polices that enable large number of students to register through this system, surely after complying with all requirements and functions needed. As a result, the end user of our system is the student. . In few words, we conclude that the produced system is applicable to be implemented in the PPU environment where it could provide facilities to the university and students in an efficient way.
CD, no of pages 164, 18657, 10/2005 تكنولوجيا المعلومات , in the store
Keywords: Registration on Line